Another road to Damascus an integrative approach to Abd al-Qadir al-Jazairi, 1808-1883 - Woerner-Powell, Tom (De Gruyter, 2017)
This text challenges Orientalist portrayals of Sufi and jihad-leader Abd al-Qadir al-Jazairi hinging on conversion from opposition to embrace of European values. Applying an inter-disciplinary approach to Arabic and European sources, this study advances a coherent, contextual, and continuous reading of his thought and actions.